Study level of physical fitness scholchildren sevens classes of general schools with the different going near organization of physical education - Лисак [Lisak I.] Ірина Вікторівна (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Defines and analyzes the level of physical fitness of students of secondary school age. Investigated the speed, agility, flexibility, strength and speed-strength qualities teenagers author compared with the normative for this age and the results that were obtained in the schools, staffed by different applications in physical training lessons. Author determined correlations between indicators of physical fitness of students for use in further research.Found that the school curriculum, which takes into account the interests and needs of students, with the best results in almost all motor tests. Found that the students of the school, where physical education into account the interests and needs of the students, have the best results in almost all motor tests. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>